A RARE CASE OF RED BAG DELIVERY IN A JENNY - DODDAGOUDAR, V; BIJURKAR, R G; TANDLE, M K (The Indian Journal of Animal Reproduction, 2017)
Red bag delivery, was found associated with a dystocia in an aborting jenny in eighth month of gestation. Thepresent report puts on record successful management of this condition in a jenny.
Keywords: Dystocia; Jenny; Placenta; Pre-mature separation; Red-bag delivery